2016
DOI: 10.3390/nu8110736
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Double-Blind Studies to Evaluate the Cognitive Effects of Inositol-Stabilized Arginine Silicate in Healthy Physically Active Adults

Abstract: Inositol-stabilized arginine silicate (ASI; Nitrosigine®) has been validated to increase levels of arginine, silicon and nitric oxide production. To evaluate potential enhancement of mental focus and clarity, ASI (1500 mg/day) was tested in two double-blind placebo-controlled crossover (DBPC-X) studies using the Trail Making Test (TMT, Parts A and B). In the two studies, healthy males took ASI for 14 and 3 days, respectively. In the first study, after 14 days of dosing, TMT B time decreased significantly from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The results demonstrated that attention and cognitive flexibility assessed by TMT-B was improved in the 6gIG, whereas no significant changes were observed in either the 3gIG or PCG. An effect of intervention on TMT-B was observed, and the 15-s improvement of 6gIG was similar to the intervention effects reported by previous intervention studies ( 32 , 33 ). The faster performance of the TMT-B suggests the improvement of the ability to concentrate on the task, pay attention to multiple tasks and memorize information needed for doing tasks, which is related with working memory.…”
Section: Discussionsupporting
confidence: 87%
“…The results demonstrated that attention and cognitive flexibility assessed by TMT-B was improved in the 6gIG, whereas no significant changes were observed in either the 3gIG or PCG. An effect of intervention on TMT-B was observed, and the 15-s improvement of 6gIG was similar to the intervention effects reported by previous intervention studies ( 32 , 33 ). The faster performance of the TMT-B suggests the improvement of the ability to concentrate on the task, pay attention to multiple tasks and memorize information needed for doing tasks, which is related with working memory.…”
Section: Discussionsupporting
confidence: 87%
“…Participants who were taking prescription medications in the month prior to the initiation of the study and/or were told by a physician to abstain or restrict caffeine and/or stimulant intake were excluded from the present study. A minimal sample size of 10 was determined based on the expectation of a 5% improvement in cognitive function markers with a corresponding power of 0.80 based on similar studies assessing nootropics on cognitive and executive function [15][16][17][18][19][20][21][22]. Participants were recruited from the university and local community via direct email and newspaper advertisements as well as by posting study flyers.…”
Section: Participantsmentioning
confidence: 99%
“…Two studies have evaluated the effects of ingesting ASI [11] and ASI + I [12] on cognitive function. In the first study, ASI supplementation (1500 mg/day for 3-days and 14-days) significantly improved the ability to perform complex cognitive tests requiring mental flexibility, processing speed and executive functioning.…”
Section: Introductionmentioning
confidence: 99%